Clinical Reasoning: A 50-Year-Old Man With Progressive Limb Weakness and Slurred Speech. (5th April 2022) - Xie, Nina; Yang, Guang; Zhang, Weiru; Xu, Hongwei; Sun, Qiying
Abstract : A 50-year-old man presented with a 9-month history of progressive left arm weakness and dysarthria. Family history showed that his parents are cousins, and one of his siblings died of motor neuron disease. Brain MRI showed T2-weighted white matter hyperintensities along the course of pyramidal tracts. Neurologic examination and EMG revealed upper and lower motor neuron signs involving the bulbar, cervical, thoracic, and lumbosacral segments, which meets the criteria of a definite amyotrophic lateral sclerosis (ALS), according to the revised EI Escorial criteria. Whole-exome genetic sequencing found 2 novel LYST missense variations, confirming the diagnosis of Chediak-Higashi syndrome (CHS), a rare autosomal recessive hematologic disorder. Our case indicates that CHS can present as ALS phenotype, and the LYST might be a novel causative gene for ALS.